Nuclear‐localized AtHSPR links abscisic acid‐dependent salt tolerance and antioxidant defense in Arabidopsis. (December 2015) - Yang, Tao; Zhang, Liang; Hao, Hongyan; Zhang, Peng; Zhu, Haowei; Cheng, Wei; Wang, Yongli; Wang, Xinyu; Wang, Chongying
Summary: Salt stress from soil or irrigation water limits plant growth. A T‐DNA insertion mutant in C24, named athspr ( Arabidopsis thaliana heat shock protein‐related ), showed several phenotypes, including reduced organ size and enhanced sensitivity to environmental cues. The athspr mutant is severely impaired under salinity levels at which wild‐type (WT) plants grow normally. AtHSPR encodes a nuclear‐localized protein with ATPase activity, and its expression was enhanced by high salinity and abscisic acid (ABA). Overexpression (OE) of AtHSPR significantly enhanced tolerance to salt stress by increasing the activities of the antioxidant system and by maintaining K + /Na + homeostasis. Quantitative RT‐PCR analyses showed that OE of AtHSPR increased the expression of ABA/stress‐responsive, salt overly sensitive ( SOS )‐related and antioxidant‐related genes. In addition, ABA content was reduced in athspr plants with or without salt stress, and exogenous ABA restored WT‐like salt tolerance to athspr plants. athspr exhibited increased leaf stomatal density and stomatal index, slower ABA‐induced stomatal closure and reduced drought tolerance relative to the WT. AtHSPR OE enhanced drought tolerance by reducing leaf water loss and stomatal aperture. Transcript profiling in athspr showed a differential salt‐stress response for genes involved in accumulation of reactive oxygen species (ROS), ABA signaling, cell death, stress response and photosynthesis. Taken together, our results suggested that AtHSPR is involved in salt tolerance in Arabidopsis through modulation of ROS levels, ABA‐dependent stomatal closure, photosynthesis and K + /Na + homeostasis. Significance Statement: Abiotic stress limits plant growth. Here we show that a nuclear protein with ATPase activity contributes to abiotic stress tolerance by scavenging reactive oxygen species, modulating ABA‐dependent stomatal closure, and affecting K + /Na + homeostasis.